Standardisation of thermal processing of cuttle fish nidamental glant - Bikash kumar pati (Department of Processing Technology, College of Fisheries, 2007)
Cuttlefish nidamental gland is a pair of flattened glands associated with the female reproductive system in cuttlefish. The glands are exported as a frozen product under the name cuttlefish roe. The procedure for thermal processing of cuttlefish nidamental gland in brine packed in tin plate can is standardised to produce a ready- to- eat product. The standardisation process essentially involved determination of optimum blanching conditions, retorting temperature, process time, processing parameters, optimum solid- liquid ratio and process levels to produce a safe product and assessment of quality changes during storage at room temperature. Cuttlefish nidamental gland in brine was packed in tin plate cans in 65 : 35 ratio (gland : brine) and thermal processed in an overpressure retort. The optimum blanching condition was found to be 5 % brine for 5 min. The retorting temperature and process time were selected as 121.10C and 25 min, respectively. The F0 value attained by the process was found to be 11.25 min with total process time of 30.54 min. The cook value meant to achieve tenderness of product was 81.54 min. The processed product was found to be commercially sterile. The product was acceptable even after 3 months of storage at room temperature with regard to all sensory attributes like appearance, colour, odour, taste, texture and overall acceptability. There were significant variation in the salt, pH and TBA values (P<0.05). The cut- out test showed a marginal increase in solid weight. The study showed that the cuttlefish nidamental gland can be used for processing ready to eat product, which can be stored at room temperature for long periods.